Chemical interactions between red P and functional groups in NiP3/CNT composite anodes for enhanced sodium storage. Issue 41 (10th October 2018) - Ihsan-Ul-Haq, Muhammad; Huang, He; Cui, Jiang; Yao, Shanshan; Wu, Junxiong; Chong, Woon Gie; Huang, Baoling; Kim, Jang-Kyo
Abstract : The chemical bonds induced by the ball milling at the heterointerfaces of NiP3 /CNT composite electrodes enhanced their sodium storage performance. Abstract : Red phosphorus has thus far the highest theoretical capacity among all known anode materials for sodium ion batteries (SIBs). However, its low electronic conductivity and large volume expansion during cycles cause rapid capacity fading, leading to poor electrochemical stability. Herein, we report a facile and scalable ball milling approach to synthesize NiP3 /carbon nanotube (CNT) composites consisting of NiP3 particles chemically bonded with functionalized CNTs. The conductive CNTs play an important role in stabilizing the composite electrode through an enhanced Na + diffusion coefficient by two orders of magnitude and six-fold reduction in its charge transfer resistance. The NiP3 /CNT composite anode delivers a high initial reversible capacity of 853 mA h g −1 with more than 80% capacity retention after 120 cycles at 200 mA g −1 and an excellent high-rate capacity of 363.8 mA h g −1 after 200 cycles at 1600 mA g −1 . The density functional theory (DFT) calculations combined with ab initio molecular dynamics (AIMD) simulations elucidate strong chemical interactions between the red P in NiP3 and the functional groups on CNTs to form P–C and P–O–C bonds by ball milling for the first time. The facile synthesis strategy devised in this study can be applied to other alloy-based composites with relatively low carbon content for use as high performance anodes for SIBs.